Orthopodomyia pulcripalpis (Diptera: Culicidae), a genus and species new to the Iranian mosquito fauna, with a review of bionomical information* - Azari-Hamidian, Shahyad; Norouzi, Behzad; Noorallahi, Ayoob (Zootaxa, 2017)
The most recent checklist of Iranian mosquitoes (Diptera: Culicidae) includes 64 species representing seven genera (Azari-Hamidian, 2007; Azari-Hamidian & Harbach, 2009). Subsequently, Oshaghi et al. (2008) found that Anopheles superpictus Grassi is two species in Iran based on the Internal Transcribed Spacer 2 (ITS2) sequences of rDNA, which were later listed as species A and B by Harbach (2013), and Djadid et al. (2009) recognized a new species of the Anopheles hyrcanus group (An. hyrcanus spIR) from southwestern Iran, also based on ITS2 sequence data. More recently, Doosti et al. (2016) reported the occurrence of Aedes albopictus (Skuse) in southeastern Iran.